COUNSELLOR PROFESSION’S COMPETENCY IN THE DISRUPTION ERA AND INSIGHTS FROM AXIOLOGY VIEW - Habibah Nurul Fazriah; Nadia Aulia Nadhirah; Nandang Budiman (OPTIMA: Journal Of Guidance and Counseling, 2023)
The era of disruption, as a result of the existence of Society 5.0. as well as the industrial revolution 4.0., make demands on counsellors to be able to adjust their competencies with all the changes that occur. Developing counsellors’ competence in the disruption era is inseparable from a series of ethics that need to be paid attention to. This article aims to provide insights for counsellors as professionals in their field, regarding the necessary competencies in the disruption era, by paying attention to each value that needs to be implemented. The research method of this article is a Systematical Literature Review (SLR) with relevant sources on the specified topic. The results of this study show that the necessary competencies for counsellors in the disruption era include aspects of technology utilization that is supported by good self-competence in terms of embedding principles of values and ethics. This article can provide direction regarding the values that counsellors need to have as professionals based on an axiological perspective, especially on ethics, in carrying out counseling services to their counselees.